2015
DOI: 10.12738/estp.2016.1.0064
|View full text |Cite
|
Sign up to set email alerts
|

A De Novo Tool to Measure the Preclinical Learning Climate of Medical Faculties in Turkey

Abstract: Although several scales are used to measure general and clinical learning climates, there are no scales that assess the preclinical learning climate. Therefore, the purpose of this study was to develop an effective measurement tool in order to assess the preclinical learning climate. In this cross-sectional study, data were collected from 3,540 preclinical medical students of six medical faculties in Turkey. The methodology included the following activities: generate an item pool, receive expert opinions, perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
0
0
0
Order By: Relevance
“…In this review, PLCS demonstrated the highest validity evidence on the five APERA standards categories among all questionnaires (Yılmaz et al, 2016). PLCS was developed in 2016, and hence it was not identified in Soemantri et al's (2010) (Soemantri et al, 2010) and in Colbert-Getz et al's (2014) (Colbert-Getz et al, 2014 systematic reviews.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…In this review, PLCS demonstrated the highest validity evidence on the five APERA standards categories among all questionnaires (Yılmaz et al, 2016). PLCS was developed in 2016, and hence it was not identified in Soemantri et al's (2010) (Soemantri et al, 2010) and in Colbert-Getz et al's (2014) (Colbert-Getz et al, 2014 systematic reviews.…”
Section: Discussionmentioning
confidence: 81%
“…Content validity and internal structure categories were reported and assessed in most of the questionnaires, while the response process and relation to other variables measures were reported and assessed in a smaller number of studies. Only one questionnaire; the Preclinical Learning Climate Scale (PLCS) provided data on the five psychometric measures (Yılmaz et al, 2016). Furthermore, the PLCS has the highest Beckman et al (2005) total validity score among other questionnaires, followed by the Johns Hopkins Learning Environment Scale (JHLES).…”
Section: Interpretation Ofmentioning
confidence: 99%